Graphene and graphene nanocomposites for the removal of aromatic organic compounds from the water: systematic review. (9th January 2018) - Paixão, Monique Monsores; Vianna, Marco Tadeu Gomes; Marques, Marcia
Abstract: Aromatic organic pollutants are highly toxic to the human and environmental health and are considered as priority pollutants by regulatory agencies. Managing contaminated sites with organic pollutants is one of the major environmental challenges today. Of all technologies that have been proposed to remove contaminants, adsorption is recognized worldwide as an attractive option due to its versatility, wide applicability and economic viability. Recent studies report the use of graphene (GN), a recently carbon nanomaterial, and its derivatives in sorption processes for the removal of aromatic organic compounds. The present review has shown that GN structures are a promising alternative to traditional adsorbent materials, with excellent results in the removal of organic compounds from water, due to their unique structural characteristics and great adsorption capacity for organic compounds. Although, there is still a long way to go until that practical applications can be implemented.